Assessment for Learning in EBE/CLIL : a Learning-oriented Approach to Assessing English Language Skills and Curriculum Content at Early Primary Level - Xavier, Ana (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2017)
Assessment is usually viewed as an inevitable event in teachers' and learners’ lives resulting from an imposition from education systems. However, if done well, assessment can provide learners, teachers and other stakeholders with sound information about learner performance and progress which will boost learning and feed into school success. This article aims at presenting a synopsis of a Master’s dissertation conducted at Faculdade de Ciências Sociais e Humanas/Universidade Nova de Lisboa (FCSH/UNL), which was defended before a jury in early 2016 and shared at the 1st Junior Researchers in Anglo-American Studies Seal Conference, held in Porto, Portugal, in June 2016. The original dissertation discusses ways of assessing both English language and curriculum content at early primary level and aims to provide learning-oriented guidelines and a principled framework for such assessment. It is meant for learners and teachers involved in Early Bilingual Education (EBE)/Content and Language Integrated Learning (CLIL) at early primary level.